Relevansi Tasawuf Dalam Pembentukan Nalar Kritis Era Post-Truth Pada Mahasiswa STIT Balikpapan - vika manaro; Tyara Destyana; Nurut Taufik (Indonesia society of applied science, 2024)
Abstract: This study examines the role of Sufism in shaping students' thinking in the post-truth ecosystem. This study is qualitative, phenomenological, with a descriptive-analytical approach. Data were collected through semi-structured interviews, literature reviews, and institutional documents at STIT Balikpapan, with 12 informants (10 students, 1 lecturer, 1 public figure), selected using purposive and snowball sampling techniques. Data validity was tested through source triangulation. The results show that Sufism-based spiritual practices—specifically tabayyun, muhasabah, and zuhud—play a role in controlling cognitive bias and regulating emotions, thus helping students assess information more clearly, non-reactively, and responsibly in the digital space. Sufism also contributes to strengthening psychological resilience when facing information pressure, opinion polarization, and self-uncertainty during the quarter-life crisis phase. This study confirms that Sufism is not only a ritual tradition, but also an ethical-cognitive mechanism relevant to strengthening students' critical literacy and digital maturity.